Maksim Kesopanan pada Tuturan Tokoh dalam Novel Bumi Surga Karya Muhammad Irata - Verawati Ahmad; Dakia N. Djou; Sitti Rachmi Masie (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Politeness in language is an effort to avoid rudeness in social interactions. This research focuses on the use of politeness maxims in the novel Bumi Surga by Muhammad Irata. The main goal is to describe the usage of politeness maxims in the work. A pragmatic approach with Geoffrey Leech's theory serves as the research framework, utilizing a qualitative descriptive method. Data is collected from the dialogues of the characters in the novel through reading, note-taking, and classification techniques. The research results reveal the presence of 37 instances of conversations following politeness maxims: tact (5 instances), generosity (4 instances), approbation (7 instances), modesty (5 instances), agreement (7 instances), and sympathy (9 instances). The data found indicates that in the novel Bumi Surga by Muhammad Irata, most of the characters' dialogues in the story adhere to politeness maxims based on Leech's theory. Compliance with politeness maxims reflects the characters' way of life in the story, as evident in their manner of speaking and interacting with one another. This demonstrates that the author has portrayed the characters' personalities and character through their communication and adherence to the principles of politeness in the narrative.